Analisis Sifat Mekanik Bioplastik PLA–Tepung Kulit Pisang pada Beragam Suhu Pemrosesan melalui Injection Molding - Maulana, Adimashqi; Fitri Ganda, Andita Nataria; Puspitasari, Dewi; Abdulloh, Isa Yuanata (Jurnal Rekayasa Mesin, 2026)
This study analyzes the effect of injection molding processing temperature variation on mechanical properties of bioplastic based on polylactic acid (PLA) reinforced with bananapeel flour. Material was processed at three different temperatures (200°C, 225°C, 250°C) with70% PLA–30% banana peel flour composition. Tensile testing was performed using Universal Testing Machine (UTM) according to ASTM D638 Type I standard to measure tensile strength and elastic modulus. Results showed that 225°C produced the highest tensile strength of 50.96 MPa and elastic modulus of 49.96 MPa, far exceeding 200°C (27.09 MPa;21.99 MPa) and 250°C (35.97 MPa; 30.40 MPa). This research confirms that there is an optimum temperature of 225°C that produces the best balance between material structure homogeneity and matrix–filler interfacial bonding, making PLA–banana peel flour bioplastic potentially suitable as a conventional plastic substitute with competitive mechanical properties.